2023
DOI: 10.3390/medicina59010131
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of Antioxidant Enzymes SOD2 (rs4880) and GPX1 (rs1050450) Are Associated with Bladder Cancer Risk or Its Aggressiveness

Abstract: Background and Objectives: Oxidative stress induced by increased reactive oxygen species (ROS) production plays an important role in carcinogenesis. The entire urinary tract is continuously exposed to numerous potentially mutagenic environmental agents which generate ROS during their biotransformation. In first line defense against free radicals, antioxidant enzymes superoxide dismutase (SOD2) and glutathione peroxidase (GPX1) both have essential roles. Altered enzyme activity and decreased ability of neutrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Unfortunately, in our work, we did not find any correlation between 47 C > T (rs4880) SNP and the risk of BC development. On the other hand, Nikić et al (2023) and Hung et al (2004) found that the risk of urothelial BC was significantly increased among Val allele carriers compared to Ala/Ala homozygote in the Serbian and Italian populations 70 , 71 . Moreover, this risk was even greater in smokers with at least one variant of the SOD2 Val allele 70 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, in our work, we did not find any correlation between 47 C > T (rs4880) SNP and the risk of BC development. On the other hand, Nikić et al (2023) and Hung et al (2004) found that the risk of urothelial BC was significantly increased among Val allele carriers compared to Ala/Ala homozygote in the Serbian and Italian populations 70 , 71 . Moreover, this risk was even greater in smokers with at least one variant of the SOD2 Val allele 70 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Nikić et al (2023) and Hung et al (2004) found that the risk of urothelial BC was significantly increased among Val allele carriers compared to Ala/Ala homozygote in the Serbian and Italian populations 70 , 71 . Moreover, this risk was even greater in smokers with at least one variant of the SOD2 Val allele 70 . However, the results of a meta-analysis by Cao et al (2014) similar to our findings, showed no significant association between the SOD2 polymorphism and the risk of bladder cancer 72 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies investigated bladder cancer. A study in the Japanese population showed that the rs1050450 Pro/Leu genotype was highly associated with advanced tumor stage and increased the risk of bladder cancer compared with the control group [57]. The Ecuador sub-population that carries this polymorphism presented 3.8 times greater probability of developing bladder cancer than controls [53].…”
Section: Selenoproteins and Their Polymorphismsmentioning
confidence: 99%
“…The GPX1 gene located on the nuclear chromosome 3p21.3 encodes for the most representative and abundant enzyme of the family: GPX1 [ 75 ]. The presence of the functional SNP rs1050450 on Gpx1 gene, induces the substitution of a cytosine with a thymine resulting in the replacement of a leucine with a proline at position 198 [ 76 ].…”
Section: Snps and Their Involvement In Oxidative Stressmentioning
confidence: 99%